Strategi Pengembangan Usaha Ternak Sapi Bali di Kecamatan Kajuara Kabupaten Bone - Astati, Astati (Universitas Islam Negeri Alauddin Makassar, 2025)
Bone Regenc, is one of the regions for Bali cattle development in South Sulawesi. Sustainable Bali cattle development is influenced by internal and external factors. Therefore, effective steps and strategies are required to manage these factors. This research was conducted in Bulu Tanah Village, Kajuara Sub-district, with the aim of analyzing the factors influencing the development of Bali cattle farming using a Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis. Internal and external factors were analyzed using the Internal External (IE) matrix to obtain the SWOT matrix. The research employed a qualitative approach, with data sourced from seven farmers, one village official, one artificial insemination (AI) officer, and one representative from the Livestock and Animal Health Office of Bone Regency. The total IFE matrix score was 3.18, while the total EFE matrix score was 3.36, indicating that Bali cattle farming development in Bulu Tanah Village, Kajuara District, Bone Regency, is relatively effective in responding to opportunities and mitigating threats.The alternative strategies proposed to sustain and develop Bali cattle farming in the region include: enhancing motivation for Bali cattle farming, providing market information, establishing policies for disease control, improving livestock facilities and infrastructure, strengthening farmer training and support services, building cooperative relationships with the government and cooperatives, enhancing vaccine and AI services, creating a conducive business environment, increasing farmers’ awareness of livestock diseases, encouraging investor interest in collaboration, improving skills in livestock product management, and offering technological training for farmers through workshops.